2020
DOI: 10.1002/iub.2365
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GAS5 sponges miR‐362‐5p to promote sensitivity of thyroid cancer cells to 131I by upregulating SMG1

Abstract: This study aims to investigate the role of lncRNA growth arrest-specific transcript 5 (GAS5)/miR-362-5p/suppressor of morphogenesis in the genitalia 1 (SMG1) axis in 131 I-resistance in thyroid cancer (TC). GAS5, miR-362-5p, and SMG1 expression in TC tissues was assessed and the 131 I-resistant TC cells were established, which were treated with altered GAS5, miR-362-5p, and SMG1. The proliferation and apoptosis of 131 I-resistant TC cells were detected, and the expression of Akt/mTOR signaling pathway-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…Mechanically, the circPPP1CB/miR-1307-3p axis directly targeted SMG1 to modulate biological functions. SMG1, a member of the phosphoinositide 3-kinaserelated kinases family, acted as a novel tumor suppressor in various human cancers (Du et al, 2014;Mai et al, 2019;Yin et al, 2019;Li et al, 2020). In our study, we confirmed that SMG1 remarkably suppressed cell proliferation, migration, invasion, and tumor angiogenesis of BC.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Mechanically, the circPPP1CB/miR-1307-3p axis directly targeted SMG1 to modulate biological functions. SMG1, a member of the phosphoinositide 3-kinaserelated kinases family, acted as a novel tumor suppressor in various human cancers (Du et al, 2014;Mai et al, 2019;Yin et al, 2019;Li et al, 2020). In our study, we confirmed that SMG1 remarkably suppressed cell proliferation, migration, invasion, and tumor angiogenesis of BC.…”
Section: Discussionsupporting
confidence: 77%
“…Loss of SMG1 completely leads to early embryonic lethal, but mice with SMG1 haploinsufficiency represent a predisposition to chronic inflammation, oxidative stress, and tumorigenesis (Roberts et al, 2013). Meanwhile, a growing body of evidence has confirmed that SMG1 acted as a tumor suppressor in various human cancers (Gubanova et al, 2013;Du et al, 2014;Han et al, 2014;Zhang et al, 2018;Mai et al, 2019;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%